Local Sentiments, Global Impact: The Case of Timisoara as the European Capital of Culture in 2023 - Megan, Ovidiu; Brandas, Claudiu; Bucurean (Roiban), Roxana Nadina; Didraga, Otniel (Transformations In Business & Economics, 2024)
Measuring the impact of the European Capitals of Culture (ECoC) program on host cities has been a prominent focus and constant challenge in academic literature, with several studies exploring how the program aligns with broader European objectives and contributes to promoting European identity and unity. Since its establishment in 1985, the program of ECoC focused on fostering cultural diversity and promoting intercultural dialogue, allowing the host cities to enhance international relations and promote cultural exchange transcending national boundaries. The current paper is focused on examining the effects of Timișoara’s designation as a European Capital of Culture, providing valuable insights into the program’s broader societal influence and its effects on the fabric of urban life in Timișoara. The 2023 ECoC effects in Timișoara, Romania, were evaluated through an innovative approach wherein sentiment analysis was integrated, leveraging data from the city’s social media platforms.